Pengaruh Kekuatan Otot Tungkai, Koordinasi Mata-Tangan Dan Konsentrasi Terhadap Kemampuan Free Throw Shoot Pada Atlet Bolabasket Putera Bengkulu Selatan - Nadira Mifta Sawiya; Yendrizal Yendrizal; Didin Tohidin; Hendri Neldi (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2022)
The problem in this study is the lack of free throw shoot skills in South Bengkulu male basketball athletes. This study aims to observe and analyze the direct and indirect effects of leg muscle strength, eye-hand coordination, and concentration on the free throw shoot skills of Bengkulu Selatan male basketball athletes. The research method is a quantitative method using a path analysis approach. The sampling technique is total sampling technique, consist of 30 athletes from all members of the population. The data analysis technique used is a path analysis approach. The results of this study indicated: 1) There is a direct influence of leg muscle strength on the free throw shoot skills of Bengkulu Selatan male basketball athletes, 2) There is a direct effect of eye-hand coordination on the free throw shoot skills of Bengkulu Selatan male basketball athletes, 3) There is no direct influence of concentration on the free throw shoot skills of Bengkulu Selatan male basketball athletes, 4) There is an indirect effect of leg muscle strength through concentration on the free throw shoot skills of Bengkulu Selatan male basketball athletes, 5) There is no indirect effect of eye-hand coordination through concentration on free throw shoot skills of Bengkulu Selatan male basketball athletes, 6) There is no direct effect of leg muscle strength, eye-hand coordination and concentration simultaneously on free throw shoot skills of Bengkulu Selatan male basketball athletes.